Analisis Minat Mereferensikan Listrik Pintar Yang Dipengaruhi Kualitas Layanan Dan Kepuasan Konsumen - Sidjabat, Daniel Benito (Universitas Sam Ratulangi, 2014)
The Purpose of this research was to determine the significant effect between service quality and customer satisfaction against interests of referencing the smart electricity usage in Manado City. The data used primary data collected through questionnaires to 100 consumers of smart electricity users. The results of data analyze obtained by multiple linear regression analysis. F count is 18.522 and a significance value of 5%, degrees of freedom df1 = 2 and df2 (100-2-1) = 97 where n is the number of respondents, k is the number of independent variables, the obtained value of F Table is 0.024. in comparison, the calculated F value is greater than the F table value (18.522 > 0.024), as the result H0 is rejected. It can be concluded that there is significant influence between quality of service (X1) and customer satisfaction (X2) against the interest of referencing the smart electricity usage in Manado City. Keywords: Quality of Service, Customer Satisfaction, and Interests Referencing.